IMPLEMENTING THE TAKE AND GIVE METHOD TO ENHANCE ENGLISH VOCABULARY AMONG STUDENTS - Maesyarah, Ummul; Muliati, A.; Ariyani, Amra (Universitas Negeri Makassar, 2025)
This study aims to determine whether or not the Take and Give method in enhances English vocabulary among students at SMPS DDI Mattoanging, Bantaeng. Employing a quantitative research approach, the investigation uses a pre-experimental design involving pre-test and post-test evaluations to measure the development of students' vocabulary proficiency. The results indicate a significant improvement, with the average score rising from 49.48 in the pre-test to 86.43 in the post-test. A paired sample t-test was conducted and produced a t-score of 9.728 with a p-value of 0.000, confirming a statistically significant difference between the two sets of scores. Additionally, the normalized gain (N-Gain) analysis yielded an average of 0.6931, suggesting that most students achieved considerable progress. These findings confirm that the Take and Give method is a successful approach for boosting students’ English vocabulary skills.